Pengembangan Media Pembelajaran Foldable Smart Board dalam Materi Tata Surya untuk Mendukung Minat Belajar Siswa Kelas V SD Negeri Itik Randai - Priyamita, Bintang; Satria Jaya, Wayan; Elvadola, Connyta (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2025)
This study aims to determine the development, feasibility, educator response, learner response and effectiveness of Foldable smart board Learning Media in Solar System Material to Support Learning Interest of Grade V Students of Itik Randai State Elementary School. The research method used is R&D (research and development) and through the ADDIE development procedure which consists of Analyze, Design, Develop, Implement, and Evaluate. Product validation was carried out by material expert validators who stated that the Foldable smart board Learning Media product developed obtained a percentage of 89% with the interpretation criteria of “very feasible”, then the results of media expert validation stated that the Foldable smart board Learning Media product developed obtained a percentage of 100% with the interpretation criteria of “very feasible”. While the educator's response obtained a percentage value of 95%, with the interpretation criteria “very interesting”, then the response of students in the small group trial obtained a percentage value of 99%, with the interpretation criteria “very interesting” and in the field trial obtained a percentage value of 94% with the interpretation criteria “very interesting” while for the product effectiveness test in terms of assigning pretest and posttest questions obtained a percentage value of 74%, with the interpretation criteria “effective”. Development of Foldable smart board Learning Media in Solar System Material to Support Learning Interest of Grade V Students of Itik Randai State Elementary School using the research and development (R&D) research method, it can be concluded that the use of Foldable smart board learning media is very feasible and effective to use as learning media.